Diagnostic Interpretation Guidance for Pediatric Enteric Pathogens: A Modified Delphi Consensus Process. (27th September 2018) - Stang, Antonia S.; Trudeau, Melanie; Vanderkooi, Otto G.; Lee, Bonita E.; Chui, Linda; Pang, Xiao-Li; Allen, Vanessa; Burnham, Carey-Ann D.; Goldfarb, David M.; MacDonald, Judy; Parsons, Brendon; Petrich, Astrid; et al.
Abstract : Background . We sought to develop diagnostic test guidance definitions for pediatric enteric infections to facilitate the interpretation of positive test results in the era of multianalyte molecular diagnostic test platforms. Methods . We employed a systematic, two-phase, modified Delphi consensus process consisting of three web-based surveys and an expert panel face-to-face meeting. In phase 1, we surveyed an advisory panel of North American experts to select pathogens requiring diagnostic test guidance definition development. In phase 2, we convened a 14-member expert panel to develop, refine, and select the final definitions through two web-based questionnaires interspersed with a face-to-face meeting. Both questionnaires asked panelists to rate the degree to which they agreed that if the definition is met the pathogen is likely to be causative of clinical illness. Results . The advisory panel survey identified 19 pathogens requiring definitions. In the expert panel premeeting survey, 13 of the 19 definitions evaluated were rated as being highly likely ("agree" or "strongly agree") to be responsible for acute gastroenteritis symptoms by ≥67% of respondent panel members. The definitions for the remaining six pathogens ( Aeromonas, Clostridium difficile, Edwardsiella, nonenteric adenovirus, astrovirus, and Entamoeba histolytica ) were indeterminate. After the expert panel meeting, only two of the modified definitions, C. difficile and E. histolytica/dispar, failed to achieve the a priori specified threshold of ≥67% agreement. Conclusions. We developed diagnostic test guidance definitions to assist healthcare providers for 17 enteric pathogens. We identified two pathogens that require further research and definition development.